Effect of dietary cholesterol on ovarian development of Chinese mitten crabs (Eriocheir sinensis) - Huixing Guo; Mangmang Wang; Xi Wang; Kang Xiao; Yangyang Huang; Haokun Hua; Wei Xiong; Wenbin Liu; Kenneth Prudence Abasubong; Wei Qiang; Cheng Chi; Guangzhen Jiang (Frontiers in Marine Science, 2022)
This study was conducted to evaluate the effect of cholesterol (CHO) on ovarian development of Eriocheir sinensis through a feeding trial. Crabs (average weight 43.35 ± 0.05 g) were randomly fed with one of three diets: 0% CHO, 0.4% CHO and 1.6% CHO for 16 weeks. Results indicated that the hepatosomatic index (HSI) and gonad index (GSI) of crabs fed with 0.4% CHO diet were significantly higher than those in the control group. ( P < 0.05). Meanwhile, 0.4% CHO can significantly increase the gene expression of vtg and vgr in ovary ( P < 0.05), thus promoting the accumulation of Vtg. The protein expression of MEK1/2, ERK, p-ERK1/2, Cyclin B and CDC2 were significantly increased in the 0.4% CHO group, therefore dietary CHO might promote oocyte maturation by activating MAPK signal pathway and cooperating with maturation promoting factor (MPF). Further exploration results showed that 0.4% CHO was able to significantly up-regulate the protein expression of STAR and SR-B1 to promote the transport of CHO to ovary, thereby providing sufficient substrates for estradiol (E 2 ) synthesis. In addition, the results in vivo and in vitro shown that CHO could regulate the activities of enzymes such as CYP11A1 and CYP19A1 through the cAMP-PKA-CREB/SF-1 signal pathway and then affects the level of E 2 in the organism. In summary, supplementing the appropriate amount of CHO in the diet can improve the E 2 level of the organism, thus increasing the accumulation of nutrients in the ovary, promoting the completion of meiosis, and finally achieving the purpose of promoting ovarian maturation.